Detection of Leishmania Major by ITS gene and its effect on the CCR7 gene expression of the human host - Alia kathem salim; Sarah Basheer; Azhaar Mousa Jaffar; Saja Tawfeek Jassim; Zaid Khalid Alani (International Journal of Medical Toxicology and Legal Medicine, 2025)
Leishmaniasis is among the most overlooked contagious illnesses, affecting around 12 million individuals and more than 350 million people at risk of infection. A total of 60 skin and mucosal lesion biopsy specimens were taken from people with clinically suspected CL in exposed part of the body mostly in the face, upper limbs, lower limbs, and before treatment. The biopsy samples were preserved in absolute ethanol and stored at room temperature from various ages, attended hospitals and health centres in the Governorate of Baghdad. The results showed out of those 60 samples 46 patients diagnosed clinically by special dermatologist as CL. And those 60 were tested by RT-PCR and 4 of the negative samples gave a positive results and only 35 samples of those samples that described as positive gave a positive results by the RT-PCR the other were negative, and the gene expression results showed an increased level of CCR7 gene expression in the positive subjects than the negative subjects.